A characterization of single‐peaked preferences via random social choice functions - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2016)
This paper proves the following result: every path-connected domain of preferences that admits a strategy-proof, unanimous, tops-only random social choice function satisfying a compromise property is single-peaked. Conversely, every single-peaked domain admits a random social choice function satisfying these properties. Single-peakedness is defined with respect to arbitrary trees. The paper provides a justification of the salience of single-peaked preferences and evidence in favor of the Gul conjecture (Barber\303\240 2010).